1996
DOI: 10.1152/jn.1996.76.6.3798
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of group II and group III mGluRs as autoreceptors at lateral and medial perforant path synapses

Abstract: 1. Previous reports have shown that group III metabotropic glutamate receptors (mGluRs) serve as autoreceptors at the lateral perforant path, but to date there has been no rigorous determination of the roles of other mGluRs as autoreceptors at this synapse. Furthermore, it is not known which of the mGluR subtypes serve as autoreceptors at the medial perforant path synapse. With the use of whole cell patch-clamp and field excitatory postsynaptic potential (fEPSP) recording techniques, we examined the groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
133
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(148 citation statements)
references
References 0 publications
14
133
1
Order By: Relevance
“…MPP, but not MCF, are sensitive to inhibition by group II metabotropic glutamate receptor (mGluR) agonists. Consistent with a previous report (Macek et al, 1996), we found that 1 μM DCG-IV strongly reduced MPP-EPSC by 74.7 ± 1.2 % at 10-15 minutes post drug application (n = 3, p<0.01; Figure 1B). In contrast, DCG-IV at this concentration had no effect on MCF-EPSC (102.9 ± 6.2 % of baseline, p>0.05).…”
Section: Methodssupporting
confidence: 93%
“…MPP, but not MCF, are sensitive to inhibition by group II metabotropic glutamate receptor (mGluR) agonists. Consistent with a previous report (Macek et al, 1996), we found that 1 μM DCG-IV strongly reduced MPP-EPSC by 74.7 ± 1.2 % at 10-15 minutes post drug application (n = 3, p<0.01; Figure 1B). In contrast, DCG-IV at this concentration had no effect on MCF-EPSC (102.9 ± 6.2 % of baseline, p>0.05).…”
Section: Methodssupporting
confidence: 93%
“…Our results extend these earlier observations by showing that presynaptic mGluRs inhibit thalamocortical synapses and that group II mGluRs mediate the inhibition in developing mice. Previous reports indicate that mGluRs can be either maintained into adulthood (Macek et al, 1996, Yokoi et al, 1996, Flavin et al, 2000 or lost during development (Baskys and Malenka, 1991, Ross et al, 2000, Doherty et al, 2004. Therefore, it is also possible that the group II mGluRmediated modulation of thalamocortical EPSCs is important only during development and does not occur in the adult brain despite the expression of group II mGluRs in the barrels of adult rats and mice (Ohishi et al, 1998, Muñoz et al, 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemical and physiological analyses have previously shown that glutamatergic transmission from MPP and LPP onto excitatory dentate granule cells, which have dendritic fields spanning the entire ML, are specifically inhibited by group II and III presynaptic metabotropic glutamate receptors (mGlus), respectively (Macek et al, 1996). Because OML interneurons only possess dendrites in the OML, not in the MML, and the opposite is true for IML interneurons (Fig.…”
Section: Inhibition Of Excitatory Transmission Onto Developing Oml Anmentioning
confidence: 99%